Development of disposable microfluidic devices for bioanalytical applications - Mendes, Geovana de Melo (2024)
This thesis was conducted as part of a joint supervision between the Universidade Federal de Goiás (Goiânia, Brazil) and Chimie ParisTech PSL. Initiated in Brazil at the onset of the pandemic, the work developed during the Ph.D. at the Brazilian institution focused on developing LAMP-based methodologies for COVID-19 diagnosis. Loop-mediated isothermal amplification (RT-LAMP) was used to create a simple and low-cost test during the COVID-19 pandemic. This test was implemented at the point of care in an overwhelmed hospital where standard tests were not feasible, providing rapid and accurate diagnoses. Additionally, we proposed a non-invasive tracking method based on RNA extracted from the saliva of essential workers during the pandemic, which proved practical and effective for frequent testing. The preliminary transposition of this methodology to a paper-based platform showed promising results for realtime monitoring of infections, particularly SARS-CoV-2, at the point of care. Within the scope of the cotutella, subsequent work was carried out in the French laboratory to develop and optimize a paper-based platform for protein isoelectric focusing, aiming to integrate proteomic analysis steps into a microdevice. In this thesis, we developed diagnostic systems for biomolecules applied or applicable at the point of care. For protein analysis, isoelectric focusing on a paper-based platform allowed precise and reproducible protein separation, including in real samples, with acceptable resolution and efficiency. This system represents a significant step forward in a broader project aimed at integrating all proteomic steps into a single chip. The successful development of biomolecule analysis methods prioritizing cost-effectiveness, speed, and simplicity highlights the potential of paper as a platform for these diagnostic tests. Paper proved to be a suitable and accessible platform for conducting these tests, emphasizing its potential in resource-limited settings.